1990
DOI: 10.1007/bf00006844
|View full text |Cite
|
Sign up to set email alerts
|

Species richness in tropical fresh waters of Australia

Abstract: General ecological expectations about the relationship between latitude and species richness are that at low latitudes (the tropics) species richness is greater than at higher latitudes (temperate and polar regions). Recent work suggests that this may not be the case for several habitat types and biological groups in Australia. Results are conflicting: on present evidence (admittedly sparse) it appears that in Australian tropical fresh waters species richness is generally depressed in zooplankton and littoral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…We have seen the rapid growth of data on the systematics and ecology of tropical zooplankton on all continents including most recently in Australia (Shiel & Williams, 1990, Timms & Morton, 1988 . Shiel & Williams (1990) found no evidence that tropical Australian zooplankton is more diverse than temperate Australian zooplankton .…”
Section: Comments and Discussionmentioning
confidence: 99%
“…We have seen the rapid growth of data on the systematics and ecology of tropical zooplankton on all continents including most recently in Australia (Shiel & Williams, 1990, Timms & Morton, 1988 . Shiel & Williams (1990) found no evidence that tropical Australian zooplankton is more diverse than temperate Australian zooplankton .…”
Section: Comments and Discussionmentioning
confidence: 99%
“…Later studies were reviewed by Shiel & Williams (1990) . Comparable rotifer species diversity was recorded in temperate River Murray billabongs during a 1988-89 study, when > 200 species were identified from weekly plankton samples from one .…”
Section: Introductionmentioning
confidence: 99%
“…Across all taxonomic groups, more data are required before making accurate comparisons with the invertebrate fauna in other climatic zones, both in Australia and elsewhere (Shiel and Williams, 1990;Humphrey and Dostine, 1994). Nevertheless, mayfl y (Ephemeroptera) and caddisfl y (Trichoptera) data have been used in comparative global zoogeographical studies (Vinson and Hawkins, 2003), while Cranston (2000) reported high diversity of chironomid fl ies in both the wet and wet-dry tropics of Australia compared with temperate Australia.…”
Section: Aquatic Invertebratesmentioning
confidence: 99%
“…When this recent colonisation of freshwater habitats is combined with the small area of freshwater habitats on the Australian continent it is not surprising that the species richness of the continent (302 species) is very low by global standards (Allen et al, 2002).The diversity of freshwater fi sh is higher in the tropics compared to temperate regions of Australia. Shiel and Williams (1990) suggested that periods of extreme aridity in the southern temperate areas and ease of migration of new species from marine to freshwaters as a result of greater length and low-gradient of tropical rivers were most likely to determine species richness of freshwater fi sh. However, Bishop and Forbes (1991) and more recently Unmack (2001) have suggested an evolutionary explanation arguing that freshwater fi sh diversity in Australia is a refl ection of the fi sh diversity in adjacent seas and this is greater in the tropics.…”
Section: Fishesmentioning
confidence: 99%